2016
DOI: 10.1021/acs.jproteome.6b00691
|View full text |Cite
|
Sign up to set email alerts
|

Combining Deep Sequencing, Proteomics, Phosphoproteomics, and Functional Screens To Discover Novel Regulators of Sphingolipid Homeostasis

Abstract: Sphingolipids (SLs) are essential components of cell membranes and are broad-range bioactive signaling molecules. SL levels must be tightly regulated as imbalances affect cellular function and contribute to pathologies ranging from neurodegenerative and metabolic disorders to cancer and aging. Deciphering how SL homeostasis is maintained and uncovering new regulators is required for understanding lipid biology and for identifying new targets for therapeutic interventions. Here we combine omics technologies to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
3
7
0
Order By: Relevance
“…Rtg1/3 likely also governs other steps in the production of sphingolipids because deletion of the rtg genes resulted in the alteration of the ratio of 42-and 44-carbon species in all complex sphingolipids ( Figure 1D). Most gene products known to be involved in sphingolipid biosynthesis appear to be regulated at post-translational levels in S. cerevisiae (Lebesgue et al, 2017). Consistent with this notion, the levels of the majority of C. albicans transcripts encoding sphingolipid biosynthesis enzymes remained unchanged after myriocin-induced sphingolipid depletion ( Figure 3A).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Rtg1/3 likely also governs other steps in the production of sphingolipids because deletion of the rtg genes resulted in the alteration of the ratio of 42-and 44-carbon species in all complex sphingolipids ( Figure 1D). Most gene products known to be involved in sphingolipid biosynthesis appear to be regulated at post-translational levels in S. cerevisiae (Lebesgue et al, 2017). Consistent with this notion, the levels of the majority of C. albicans transcripts encoding sphingolipid biosynthesis enzymes remained unchanged after myriocin-induced sphingolipid depletion ( Figure 3A).…”
Section: Discussionsupporting
confidence: 69%
“…Our RNA-seq experiment comparing myriocin-treated versus untreated C. albicans cells identified 255 protein-coding transcripts that altered their expression in response to the drug (Àlog 10 p > 10 and expression changes >2-fold; Figure 3A; Table S3; 289 targets at p < 0.001 and expression changes >2-fold). Transcriptome studies in S. cerevisiae (Lebesgue et al, 2017;Liu et al, 2013) have found that myriocin does not cause major changes in the transcripts that encode enzymes mediating sphingolipid biosynthesis (it was in the phosphoproteome where relevant changes were more likely to occur; Lebesgue et al, 2017). Both Lebesgue et al (2017) and Liu et al, (2013) found that the predominant effect at the transcriptome level was in stress, ribosome, and RNA processing genes.…”
Section: Sphingolipid Depletion and Tor Inhibition Have Opposite Effementioning
confidence: 99%
See 1 more Smart Citation
“…For example, proteomewide mass spectrometry studies have found that all three of the Gin4-related kinases are strongly hyperphosphorylated on multiple sites in rts1∆ cells, and that synthesis of ceramides influences Gin4 phosphorylation (Zapata et al 2014;Lebesgue et al 2017).…”
Section: Elm1 and The Gin4-related Kinases Do Not Influence Torc2 Sigmentioning
confidence: 99%
“…Several observations suggest that the Gin4-related kinases are influenced by Rts1-dependent feedback signals from the TORC2 network. For example, proteomewide mass spectrometry studies have found that all three of the Gin4-related kinases are strongly hyperphosphorylated on multiple sites in rts1∆ cells, and that synthesis of ceramides influences Gin4 phosphorylation (Zapata et al 2014;Lebesgue et al 2017). In addition, the increased TORC2 signaling caused by rts1∆ is dependent upon the Gin4related kinases.…”
Section: Elm1 and The Gin4-related Kinases Do Not Influence Torc2 Sigmentioning
confidence: 99%